A porous and air gap elastomeric dielectric layer for wearable capacitive pressure sensor with high sensitivity and a wide detection range. Issue 33 (20th July 2020) - Li, Wei; Jin, Xin; Zheng, Yide; Chang, Xudong; Wang, Wenyu; Lin, Tong; Zheng, Fan; Onyilagha, Obiora; Zhu, Zhengtao
Abstract : Capacitive sensor combining highly porous PDMS and rough polypyrrole electrodes improves the device range and sensitivity. Abstract : A flexible and highly sensitive capacitive sensor capable of detecting pressure over a wide range was prepared using an elastomeric dielectric layer with high porosity and air gaps sandwiched between conducting polymer/filter paper electrodes. Porous polydimethylsiloxane (PDMS) with air gaps ( i.e. through holes) was prepared by using NaCl powders and an array of metal pins as a template during the curing process. An as-fabricated capacitive sensor based on the PDMS layer with ∼60% porosity and an array of 6 × 6 air gaps with diameters of ∼850 μm showed high sensitivity for the pressure range from ∼5 Pa to 1 MPa, a quick response time and good durability. Potential applications of the capacitive pressure sensor in human motion monitoring and spatial pressure mapping were demonstrated.